Pengembangan Bahan Lerak Menjadi Cairan Deterjen Pembersih Serbaguna - Sahara, Siti; Maharani, Erika Dian; Saifana, Najla (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The evolution of people's patterns and direction of thinking in increasing awareness of protecting the environment has changed due to advances in public education. Increased awareness of environmental problems encourages people to look for alternative environmentally friendly products that are free from dangerous chemicals. As awareness of environmental issues increases, many people are looking for environmentally friendly alternatives for everyday products, including cleaners for household and kitchen appliances. Lerak fruit (Sapindus rarak DC.) emerged as a potential solution. The use of lerak fruit as soap has been around since ancient times, even before modern soap was discovered. The saponin content of lerak fruit can be used as an anti-microbial agent and can be used as an environmentally friendly multi-purpose cleaning detergent. It is hoped that this experiment will provide useful information for the development and utilization of lerak material as an environmentally friendly multi- purpose cleaning detergent.